PERJALANAN PAHLAWAN WANITA SEPERTI TEREFLEKSI DALAM FILM â€œZOOTOPIAâ€ PRODUKSI CLARK SPENCER - Ruauw, Wulan Melisa; Sigarlaki, Stephani J.; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â This research is entitled â€œPerjalanan Pahlawan Wanita seperti Terefleksi dalam Film Zootopia Produksi Clark Spencerâ€ it is intended as a requirement to accomplish the bachelorâ€Ÿs degree at Faculty of Humanities Sam Ratulangi University Manado. Thisresearch focus on the heroineâ€Ÿs journey of Judy Hopps. The purposes of this research are to identify, classify, analyze, and describe the heroineâ€Ÿs journey of Judy Hopps. This research used descriptive qualitative method by Johnson (1953). In identifying, classifying the writer used theory plot by Freytag (1895) and theory of heroineâ€Ÿs journey by Murdock (1990) and in analyzing the data the writer used theories of character by Eder et. al (2010) and film by Synder (2011) . The results of this research are Judy has gone through all of the stages of the heroineâ€Ÿs journey. The heroineâ€Ÿs journey Judy had gone through was (1) separationfrom the feminine, (2) identification with the masculine, (3) road of trials: meeting ogres and dragons, (4) finding the boon of success, (5) awakening to feelings of spiritual aridity: death, (6) initiation and descent to the Goddess, (7) urgent yearning to reconnect with the feminine, (8) healing the mother/daughter split, (9) healing the wounded masculine, (10) integration of masculine and feminine.Keywords: Heroineâ€™s Journey, Zootopia, Character, Setting, Plot, Film